The Relationship between Learning Styles and Learning Interests: A Study on Fourth Grade Social Studies Students - Aulia, Nisa; Gusrayani, Diah; Nugraha, Rana Gustian (Universitas Veteran Bangun Nusantara, 2024)
This research aims to analyze the relationship between learning styles and students' interest in learning in class IV social studies. The method used in this research is a descriptive qualitative method with a case study approach. The results of this research are: The research participants consisted of 29 students and 1 class IV teacher at SDN Sukaraja I Sumedang. The research instruments used were observation, interviews and documentation studies. The results and discussion obtained show that learning style is very influential on students' interest in learning in that the percentage of students who have a visual learning style is 14%, while auditory is 52% and kinesthetic is 34%. Thus, the results of the study explain that class IV students at SDN Sukaraja I Sumedang tend to have auditory and kinesthetic learning styles. This can be seen from the enthusiasm of the students in paying attention to the teacher when carrying out differentiated learning activities, especially in social studies learning.